The Compound U18666A Inhibits the Intoxication of Cells by Clostridioides difficile Toxins TcdA and TcdB - Papatheodorou, Panagiotis; Kindig, Selina; Badilla-Lobo, Adriana; Fischer, Stephan; Durgun, Ebru; Thuraisingam, Tharani; Witte, Alexander; Song, Shuo; Aktories, Klaus; Chaves-Olarte, Esteban; Rodríguez, César; Barth, Holger (Frontiers in Microbiology, 2021)
The intestinal pathogen Clostridioides (C.) difficile is a major cause of diarrhea both in hospitals and outpatient in industrialized countries. This bacterium produces two large exotoxins, toxin A (TcdA) and toxin B (TcdB), which are directly responsible for the onset of clinical symptoms of C. difficile-associated diseases (CDADs), such as antibiotics-associated diarrhea and the severe, life-threatening pseudomembranous colitis. Both toxins are multidomain proteins and taken up into host eukaryotic cells via receptor-mediated endocytosis. Within the cell, TcdA and TcdB inactivate Rho and/or Ras protein family members by glucosylation, which eventually results in cell death. The cytotoxic mode of action of the toxins is the main reason for the disease. Thus, compounds capable of inhibiting the cellular uptake and/or mode-of-action of both toxins are of high therapeutic interest. Recently, we found that the sterol regulatory element-binding protein 2 (SREBP-2) pathway, which regulates cholesterol content in membranes, is crucial for the intoxication of cells by TcdA and TcdB (Papatheodorou et al., 2019, FASEB J). Furthermore, it has been shown that membrane cholesterol is required for TcdA- as well as TcdB-mediated pore formation in endosomal membranes, which is a key step during the translocation of the glucosyltransferase domain of both toxins from endocytic vesicles into the cytosol of host cells (Giesemann et al., 2006, J Biol Chem). In the current study, we demonstrate that intoxication by TcdA and TcdB is diminished in cultured cells preincubated with the compound U18666A, an established inhibitor of cholesterol biosynthesis and/or intracellular transport. U18666A-pretreated cells were also less sensitive against TcdA and TcdB variants from the epidemic NAP1/027 C. difficile strain. Our study corroborates the crucial role of membrane cholesterol for cell entry of TcdA and TcdB, thus providing a valuable basis for the development of novel antitoxin strategies in the context of CDADs.